2013
DOI: 10.1186/1477-7525-11-129
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life of children and adolescents with mental disorders

Abstract: BackgroundThe aim was to assess the association of internalising and externalising pathology with the child’s health-related quality of life (QoL), and to determine which child and environmental characteristics beyond pathology were related to poor QoL.MethodsData was obtained for 120 children and adolescents (aged 6 to 18) commencing outpatient psychotherapy treatment. Parents and children (aged 11 years and older) filled out questionnaires. QoL was measured with the KIDSCREEN-27.ResultsQoL was more strongly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 12 publications
3
28
1
2
Order By: Relevance
“…In particular, the use of these questionnaires for studies of HRQOL of children with mental health problems has increased [18][19][20]. Since mental health problems such as attention deficits, learning difficulties, and conduct problems can strongly impact HRQOL at school and at home in everyday life [19,21], in addition to the potential difficulties in maintaining attention when performing tasks [22], a brief and reliable HRQOL measure is indispensable for evaluating therapeutic and educational interventions.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the use of these questionnaires for studies of HRQOL of children with mental health problems has increased [18][19][20]. Since mental health problems such as attention deficits, learning difficulties, and conduct problems can strongly impact HRQOL at school and at home in everyday life [19,21], in addition to the potential difficulties in maintaining attention when performing tasks [22], a brief and reliable HRQOL measure is indispensable for evaluating therapeutic and educational interventions.…”
Section: Introductionmentioning
confidence: 99%
“…A developmental approach to QL assessment asserts the same recommendation for studies involving school-aged children and adolescents to avoid the inaccuracy of assuming the former group to be "small adolescents" or the latter to merely be "grown up children" [7]. In fact, it has been suggested that the incorporation of QL assessments in the therapeutic process might increase in importance from childhood to adolescence because psychopathology may persist, and its impact on QL tends to increase with age [12].…”
Section: Introductionmentioning
confidence: 99%
“…Como resultado, concluiu-se que: o número de consultas que resultaram em diagnóstico e recomendação dobrou para os jovens, mas não aumentou para os adultos; o cuidado com a saúde mental infantil cresceu em maior escala que a adulta e coincidiu com o aumento do uso de medicação psicotrópica; a grande maioria dos atendimentos em saúde mental em consultório é realizada por médicos que não são psiquiatras; o número de consultas que resultaram em prescrição aumentou tanto em adultos quanto em crianças. Weitkamp et al (2013) almejavam identificar a relação entre a internalização e externalização de sintomas e a qualidade de vida relacionada à saúde de crianças e adolescentes. Verificou-se que, tanto para os pais quanto para as crianças, o bem-estar físico e psicológico influenciou a qualidade de vida, que tem uma relação mais forte com a internalização dos sintomas do que com a externalização.…”
Section: Fatores Associados a Indicadores De Transtornos Mentais Em Cunclassified